Teacher Job Satisfaction and Well-Being: Impact of School Calendar Design - Rahimi, Regina; Liston , Delores D. (Journal of Education and Practice, 2025)
Examining teachers’ job satisfaction could be key in addressing recruitment and retention within the profession (Gangone, 2024). While this is a multi-faceted concept, one newly emerging aspect of teachers’ work that is being examined is teachers’ workload and how the design of the school calendar contributes to teachers’ professional well-being. While there is not an abundance of recent research on this topic, some districts across the country are moving away from the traditional 180-day “summers off” calendar design and looking at structuring calendars that are more attractive for their school staff. This paper will explore the literature related to such school calendar designs as well as factors related to teacher job satisfaction. Then, we will highlight findings from our study in which we surveyed 120 teachers’ perceptions of their job satisfaction, with particular focus on their perceptions of how their professional well-being is or may be impacted by their workloads as related to school calendars. Their perceptions indicate school calendars that allowed for more frequent breaks would encourage their satisfaction and retention, offering a unique concept to pursue for supporting retention in the field.